4-H Marine Aquarium Adult Partner Guide - R. Prudence Caskey (EDIS)
This guide is designed to assist the adult partner with a better understanding of the Marine Aquarium Project Book, as well as enhancing youths’ learning experiences. Written by Prudence Caskey, and published by the Florida 4-H Youth Development Program, UF/IFAS Extension, May 2023.